Strategi dan Metode Pendidikan Nabi Muhammad di Fase Mekkah: Relevansi untuk Pendidikan Islam Kontemporer - Jerni Jerni Hidayah,S; Edi Yusrianto (MGMP PAI SMP BINTAN, 2025)
This study aims to examine the educational approaches and strategies used by the Prophet Muhammad SAW in conveying Islamic teachings during the Mecca phase. The Mecca period was an important phase in the history of Islamic preaching, during which the Prophet faced complex social, cultural, and political challenges. This study employs a descriptive qualitative approach using literature review methods, analysing primary sources such as the Quran, hadith, and relevant classical and contemporary literature. The findings reveal that the Prophet's educational strategies in Mecca emphasized the cultivation of faith, character development, and the promotion of values such as monotheism, patience, and noble ethics. The methods employed included a personal (individual) approach, covert (sirriyah) preaching, setting a good example (uswah hasanah), and utilizing a limited social environment such as the house of Arqam bin Abi Arqam as a centre for training. This strategy demonstrated effectiveness in shaping the early generation of Muslims who were resilient and highly committed to Islamic teachings. The educational methods used by the Prophet in Mecca remain relevant for application in contemporary education, particularly in instilling faith and Islamic education, character and moral education for foundational or basic education.